2022
DOI: 10.3389/fonc.2022.968978
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ related sexual outcomes in colorectal surgery

Abstract: BackgroundPatients undergoing colorectal surgery (CRS) have an increased risk of developing sexual disorders, attributed to different mechanisms. In this context, sexual function (SF) assessment of patients before and after surgery is essential: to identify risk factors for sexual disorders as well as to minimize their impact on overall quality of life (QoL), allowing them a satisfying relationship and sexual life.Material and methodsPatients over 18 years of age who underwent a CRS in the University Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In the study conducted by Liot et al [36], involving 72 patients with a mean age of 58 years who underwent colorectal surgery, the findings revealed a notable gender-based difference in postoperative outcomes. Men showed no significant change in sexual function, quality of life, and marital satisfaction after surgery.…”
Section: Summary Of Evidencementioning
confidence: 94%
See 1 more Smart Citation
“…In the study conducted by Liot et al [36], involving 72 patients with a mean age of 58 years who underwent colorectal surgery, the findings revealed a notable gender-based difference in postoperative outcomes. Men showed no significant change in sexual function, quality of life, and marital satisfaction after surgery.…”
Section: Summary Of Evidencementioning
confidence: 94%
“…This systematic review also identified evolving treatment strategies for EOCRC over the past decade, reflecting how these advancements could influence patient outcomes, especially in terms of sexual function. Treatments have become more aggressive and diverse, including chemotherapy, surgery, and the introduction of immunotherapy, which have had a clear impact on patients' quality of life and complications, such as sexual dysfunction [36]. These treatment modalities, while extending life expectancy and potentially enhancing disease control, have brought the importance of addressing quality of life issues, including sexual health and psychological well-being, to the forefront.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Strikingly, the survey completely omits RAI. To address the health-care inequities for people who engage in RAI, it is necessary for health-care professionals to acknowledge pleasurable and problematic RAI 4,56,57 .…”
Section: Management Of Problematic Rai Conclusionmentioning
confidence: 99%